The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1080/17445302.2013.785772
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on dynamic model testing of a deep-water Riser Support by truncated hybrid method

Abstract: A device Riser Support is designed for Chinese S-Lay vessel 'HYSY-201'. The device is used to install risers as well as subsidiary structures, such as pipeline end termination (PLET), pipeline end manifold (PLEM), in-line sled (ILS) and so on for submarine pipelines. The paper mainly elaborates the finite element analysis and dynamic experiment of the deep-water Riser Support based on a truncated hybrid model. To test the mechanical property and verify the reliability of the Riser Support, some dynamic tests w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In the model experiment, whether the dynamic characteristics of the model tower and the structural strength have enough similarity with the prototype are very important to the reliability of the prototype-related properties of the experimental model. We could simulate and compare the scaled model with the prototype to verify the similarity of the experimental scaling model [28].…”
Section: Similarity Verification Of Experimental Scaled Modelmentioning
confidence: 99%
“…In the model experiment, whether the dynamic characteristics of the model tower and the structural strength have enough similarity with the prototype are very important to the reliability of the prototype-related properties of the experimental model. We could simulate and compare the scaled model with the prototype to verify the similarity of the experimental scaling model [28].…”
Section: Similarity Verification Of Experimental Scaled Modelmentioning
confidence: 99%
“…Li and Low [14] studied the effects of the low-frequency motion of ships on the fatigue response of a steel catenary riser at the touchdown point. Guo et al [15] established a hybrid truncated model of a deepwater riser and the reliability of the model was proven by finite element simulation and experimental tests. Shiri [16] investigated the effect of the formation of a seabed trench on the fatigue resistance of steel catenary risers.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the lateral vibrations are negligible, and hence, the idea of using planar motion models seems to be a plausible approximation. Furthermore, a number of useful contributions to the analysis and design of marine risers or pipelines are available in the literature published in recent years (Ai et al, 2018;Lou et al, 2017;Park et al, 2015;Yuan et al, 2018;Khan and Ahmad, 2017;Li and Low, 2012;Guo et al, 2013;Gao et al, 2014;Gao et al, 2016;Xu et al, 2017;Bai et al, 2017;Zhang et al, 2015;Ye et al, 2014;Dong et al, 2013;Katifeoglou and Chatjigeorgiou, 2016;Park et al, 2018;Vendhan, 2014;Gu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%